Exostoma ericinum, a new glyptosternine catfish from southwestern China (Teleostei: Siluriformes: Sisoridae) - Ng, Heok Hee (Zootaxa, 2018)
A new species of glyptosternine catfish in the genus Exostoma is described in this study. The new species, E. ericinum, is known from the upper Dayingjiang (=Taping River) drainage in southwestern China and is distinguished from congeners in having an unique combination of the following characters: 42–44 vertebrae; parallel striae on anterolateral surfaces of lips and lower surface of maxillary barbel; interorbital distance 26–31% HL; preanal length 67.7–70.5% SL; body depth at anus 10.4–12.0% SL (1.4–1.9 times in caudal peduncle depth); length of adipose-fin base 39.5–43.0% SL; lacking an incision at posterior extremity of adipose-fin base; caudal peduncle length 23.2–26.2% SL; caudal peduncle depth 5.7–7.9% SL; and caudal-fin lobes with slightly concave posterior margin.